The Informal Sector Between Support and Rejection: A Reflection of Urban Poverty - boukheit, salima (Journal of Social Sciences and Humanities, 2016)
Over time and with the increasing complexity of urban problems in developing countries, the informal sector has become an inherent phenomenon and a feature of daily life in these cities. This is due to its size, in terms of the unemployed individuals it absorbs, and the diverse activities it encompasses across various functions and professions, despite their marginality. As the factors behind its emergence vary, so do its positive impacts (tackling poverty and unemployment) and negative ones. Consequently, various perspectives have emerged among researchers and policymakers alike, ranging from supporting its existence to rejecting it. Between these two conflicting views, this sector remains a reflection of the expanding circle of urban poverty in the cities of developing countries in general, and Algeria in particular.